Identification of Forest Fire Hotspots and Impact of Forest Fire on Plant Community in Col. Sher Jung National Park and Chail Wildlife Sanctuary, Himachal Pradesh, India - Sehgal, Archi; Kumar, Krishan; Rai, Nandini; Bhatt, Swati; Dhawan, V. K. (Indian Forester, 2024)
Research was conducted in two forest fire prone districts of Himachal Pradesh (Solan and Shimla). Three types of plots were laid out in protected areas of two district having different vegetation composition and structure. We used secondary data to identify Forest fire prone beats. It was observed that among 6 beats in Col. Sher Jung National Park (CSJNP), Kaludev and Marusidh beats are fire sensitive whereas for Chail Wildlife Sanctuary (CWLS), Banjani and Blossom beats prone to fire. The IVI show dominance of Shorea robusta in CSJNP for all plots while Pinus roxburghii found dominant only in fire plots of CWLS. Shannon-Wiener index for shrub, herbs, faunal diversity vary in three plots for both protected area taken understudy. The study revealed, number of fire incidences was less in CWLS but the extent of burnt area was higher than CSJNP. One way ANOVA show significant difference in Shrubs (P value= 0.03) and faunal diversity (P value =0.02) in all three plots of CWLS. In management perspective, forest department is well prepared during forest fire season (May-June) by following practices like clearance of fire lines, control burning, etc. but challenges like difficult terrain, arson fire by Gujjars, lack of awareness require effective management strategies.